AN ANALYSIS OF THE ERRORS OF THE FIRST YEAR STUDENTS OF SMK TARUNA PEKANBARU IN USING SIMPLE PRESENT TENSE IN WRITING DESCRIPTIVE TEXTS - Alhamda, Rahmat; Azhar, Fadhly; Aruan, Rumiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research is a descriptive research that was conducted based on the problem occurred at the first years students of SMK Taruna Pekanbaru; namely the students were lack in making texts using simple present tense that influence them got poor score in test. Therefore, this research was aimed to find out the dominant errors made by the first year students of SMK Taruna Pekanbaru in using simple present tense in writing descriptive text, The participants were 31 students from first years of SMK Taruna Pekanbaru. This research was conducted for about four months (January â April, 2015) and wad taken on March and April , 2015 at SMK Taruna Pekanbaru, Rajawali Sakti street No.37, Panam. In collecting the data, writer explained the subjects about the use of the simple present tense, and then writer explained about the rules in writing a descriptive text. Next, writer held a field research by preparing questions sheet and answer sheets. Each of the question sheets consisted of an outline that will guide them in writing a descriptive text and the answer sheets were for the studentsâ writing. The writer looked after the test to avoid the same writing among the students. Then writer analyzed the studentsâ works by making a list of the studentsâ errors in using the simple present tense in descriptive text. Based on thoseerrors, writer furthermore began to conduct an error analysis.Keyword: descritive texts, simple presents tense.